More-than-human perspectives in understanding embodied learning - Biljana Culibrk Fredriksen (FORMakademisk, 2020)
Abilities to learn through embodied interactions with environments are biologically imprinted in both humans and many other species in order to preserve survival of the species. By combining data from studies with young children’s and a foal’s (a newborn horse’s) experiential learning, the author shows how both humans and other-than-human learn thought self-initiated actions, embodied intra-action with their environments and considerate choices of action. The article suggests that a justification of embodied learning as crucial for survival across species could motivate deconstruction of dualisms between embodied and verbal, between human and other-than-human, and promote more holistic understanding of learning. In the times of emerging ecological challenges, embodied forms learning can cultivate ecological awareness and provide conditions for education for ecological sustainability.